2022
DOI: 10.3920/wmj2021.2685
|View full text |Cite
|
Sign up to set email alerts
|

Review of good agricultural practices for smallholder maize farmers to minimise aflatoxin contamination

Abstract: Maize is consumed world-wide as staple food, livestock feed, and industrial raw material. However, it is susceptible to fungal attack and at risk of aflatoxin contamination under certain conditions. Such contamination is a serious threat to human and animal health. Ensuring that the maize used by food industry meets standards for aflatoxin levels requires significant investment across the supply chain. Good Agricultural Practices (GAP) form a critical part of a broader, integrated strategy for reduction of afl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 119 publications
(171 reference statements)
0
9
0
Order By: Relevance
“…This can lead to plants that are easily infected by moulds, with subsequent mycotoxin production if not substituted with irrigation. Cultivation of maize, for example, in many parts of Africa, is common during the rainy season, as necessity in rain-fed systems can lead to an increase in accumulation of aflatoxins [ 54 ]. Additionally, high temperatures and drought stress have directly affected maize and the occurrence of Aspergillus flavus, favouring fungal growth, conidiation, and spore dispersal and impairing the growth and development of maize [ 17 , 19 , 20 , 21 ].…”
Section: Factors Responsible For High Levels Of Mycotoxin Contaminati...mentioning
confidence: 99%
“…This can lead to plants that are easily infected by moulds, with subsequent mycotoxin production if not substituted with irrigation. Cultivation of maize, for example, in many parts of Africa, is common during the rainy season, as necessity in rain-fed systems can lead to an increase in accumulation of aflatoxins [ 54 ]. Additionally, high temperatures and drought stress have directly affected maize and the occurrence of Aspergillus flavus, favouring fungal growth, conidiation, and spore dispersal and impairing the growth and development of maize [ 17 , 19 , 20 , 21 ].…”
Section: Factors Responsible For High Levels Of Mycotoxin Contaminati...mentioning
confidence: 99%
“…In the current study, it was found that the postharvest practices used by groundnut farmers are variable and depend on the survey area. These practices help to minimize or increase the risk of spoilage and mycotoxin contamination of groundnuts, particularly aflatoxins, as has been pointed out in numerous studies [ 14 , 17 , 46 49 ]. Overall, many suboptimal postharvest practices were identified among the groundnut farmers surveyed across Adamawa, Centre, and North Cameroon.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the increased universal demand for food, the GCC intensifies crop cultivation and production, in turn, might lead to the establishment of single-crop cultivation systems ( 56 ). Additionally, underestimating of crop rotation and plantation of susceptible crops may also increase the risk of future AFs occurrence ( 57 ).…”
Section: The Upcoming Gcc and Future Afs Contamination Risksmentioning
confidence: 99%